Dimensional Assessment of Psychopathy and Its Relationship with Physiological Responses to Empathic Images in Juvenile Offenders - Barros, Daniel M.; Dias, Alvaro M.; Serafim, Antonio; Castellana, Gustavo; Achá, Maria Fernanda; Busatto, Geraldo (Frontiers in Psychiatry, 2013)
Objective: Many psychophysiological studies investigate whether psychopaths present low levels of electrodermal activity (EDA). However, despite evidence that varying degrees of psychopathy are normally distributed in the population, there is a paucity of EDA studies evaluating dimensionally. Moreover, although lack of empathy is a cornerstone of psychopathy, there has been a lack of studies using pictures of empathic emotional content to assess psychophysiological responses. Method: We studied a population of young male delinquents (n = 30) from a detention center, using the Psychopathy Checklist Revised (PCL-R) to determine if higher levels of psychopathy were related to lesser degrees of EDA in response to emotion-eliciting pictures of empathic content. Results: There were significant correlations (p < 0.05) between latency and peak of EDA responses to unpleasant pictures and factor 1 scores, as well as between lability of EDA responses and factor 2 scores. Conclusion: These results extend previous findings indicating direct relationship between EDA and psychopathy, and suggest that separate investigations of the two PCL-R factors have the potential to unravel more complex relationships between EDA and psychopathy. Also, by demonstrating such associations using emotion-provoking stimuli with empathic content, our results provide a link between levels of psychopathy and biological indices of empathic detachment.